Konsep Gerak Dasar Sepak Bola di Sekolah Dasar: Tinjauan Keterpaduan dengan Fase Kegembiraan Kurikulum FILANESIA sebagai Panduan Pembinaan Sepak Bola Nasional - Feri Yose Rizal; Endarman Saputra; Reza Hadinata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The FILANESIA Curriculum is the official national football development guide published by the Football Association of Indonesia (PSSI), adopting FIFA's Long-Term Player Development (LTPD) framework. Within this curriculum, development is organized into age-based phases, and the earliest phase—covering ages 6–12—directly targets elementary school (SD) students. Nevertheless, no study has explicitly examined how basic football movement concepts taught in Physical Education, Sports, and Health (PJOK) at the elementary level can support and align with this phase. This article aims to analyze the alignment between basic football movement concepts in elementary PJOK and the early-age phase competency demands of the FILANESIA Curriculum, and to formulate implications for PJOK teachers' instructional practice. The study employed a qualitative approach with document analysis and conceptual study design. Primary data sources were the official FILANESIA Curriculum document, the PJOK Learning Achievement for Elementary Merdeka Curriculum, and PJOK textbooks for grades I–VI. Analysis was conducted through content comparison based on movement taxonomy, development phase mapping, and triangulation with relevant international LTPD literature. Findings identified a high degree of alignment (83.7%) between elementary PJOK basic movement indicators and FILANESIA early-age phase competencies in the locomotor and manipulative skill domains. However, gaps were found in the introduction of simple tactics (missing link of 31.4%) and game rule literacy (24.8%). This research produces a conceptual alignment map that can serve as a reference for PJOK teachers in aligning instruction with the FILANESIA Curriculum, along with concrete recommendations for developing FILANESIA-based PJOK syllabi for grades IV–VI.